Bone impact after two years of low-dose oral contraceptive use during adolescence. - Lilian Rodrigues Orsolini; Tamara Beres Lederer Goldberg; Talita Domingues Caldeirão; Carla Cristiane da Silva; Anapaula da Conceição Bisi Rizzo; Talita Poli Biason; Altamir Santos Teixeira; Helio Rubens Carvalho Nunes (PLoS ONE, 2023)
Objective Data regarding the use and effect of hormonal contraceptives on bone mass acquisition during adolescence are contradictory. The present study was designed to evaluate bone metabolism in two groups of healthy adolescents using combined oral contraceptives (COC). Methods A total of 168 adolescents were recruited from 2014 to 2020 in a non-randomized clinical trial and divided into three groups. The COC1 group used 20 μg Ethinylestradiol (EE)/150 μg Desogestrel and the COC2 group used 30 μg EE/3 mg Drospirenone over a period of two years. These groups were compared to a control group of adolescent non-COC users. The adolescents were submitted to bone densitometry by dual-energy X-ray absorptiometry and measurement of bone biomarkers, bone alkaline phosphatase (BAP), and osteocalcin (OC) at baseline and 24 months after inclusion in the study. The three groups studied were compared at the different time points by ANOVA, followed by Bonferroni's multiple comparison test. Results Incorporation of bone mass was greater in non-users at all sites analyzed (4.85 g in lumbar Bone mineral content (BMC)) when compared to adolescents of the COC1 and COC2 groups, with a respective increase of 2.15 g and loss of 0.43g in lumbar BMC (P = 0.001). When comparing subtotal BMC, the control increased 100.83 g, COC 1 increased 21.46 g, and COC 2 presented a reduction of 1.47 g (P = 0.005). The values of bone markers after 24 months are similar for BAP, being 30.51 U/L (± 11.6) for the control group, 34.95 U/L (± 10.8) for COC1, and 30.29 U/L for COC 2 (± 11.5) (P = 0.377). However, when we analyzed OC, we observed for control, COC 1, and COC 2 groups, respectively, 13.59 ng/mL (± 7.3), 6.44 ng/mL (± 4.6), and 9.48 ng/mL (± 5.9), with P = 0.003. Despite loss to follow-up occurring in the three groups, there were no significant differences between the variables in adolescents at baseline who remained in the study during the 24-month follow-up and those who were excluded or lost to follow-up. Conclusion Bone mass acquisition was compromised in healthy adolescents using combined hormonal contraceptives when compared to controls. This negative impact seems to be more pronounced in the group that used contraceptives containing 30 μg EE. Clinical trial registration http://www.ensaiosclinicos.gov.br, RBR-5h9b3c. "Low-dose combined oral contraceptive use is associated with lower bone mass in adolescents".